Radicalization and violent extremism depend on envy; conspiracy ideation, sometimes - Moncrieff, Michael; Lienard, Pierre (Frontiers in Psychology, 2023)
Emotions are conspicuous components of radicalization, violent extremism, and conspiracy ideation. Of the emotions studied for their contribution to those social pathologies, envy has been relatively unexplored. We investigate the relationship between envy, radicalization, and conspiracy ideation. Envy appears to affect core aspects of radicalization, particularly the endorsement of extremism and the acceptance of violent means to achieve one’s ends, while radicalization facilitates the adoption of conspiracy ideation, rather than the latter being a cause of radicalization. Implications for future research on radicalization and violent extremism are discussed.